2007
DOI: 10.1007/s11581-007-0098-7
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and conduction mechanism studies of PVA-orthophosphoric acid polymer electrolyte

Abstract: Polyvinyl alcohol (PVA)-based proton conducting polymer electrolytes have been prepared by the solution cast technique. The conductivity is observed to increase from 10 −9 to 10 −4 S cm −1 as a result of orthophosphoric acid (H 3 PO 4 ) addition. The plot of conductivity vs temperature shows that a phase transition occurred at 343 K in the sample PVA-33 wt% H 3 PO 4 . The β-relaxation peak is observed at 313 K. The glass transition temperature of PVA-33 wt% H 3 PO 4 is 343 K. Orthophosphoric acid seems to play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…PVA complexed with inorganic acid has been already reported by Vargas et al, and has reported the plasticization effect of acids and water in PVA [16]. Dielectric and conduction properties of PVA complexed with H 3 PO 4 have been studied by Kufian et al [17]. Dielectric properties, vibrational and NMR studies on PVA doped with H 3 PO 4 and dielectric properties on PVA doped with H 2 SO 4 have been studied by Singh et al [18,19].…”
Section: Introductionmentioning
confidence: 94%
“…PVA complexed with inorganic acid has been already reported by Vargas et al, and has reported the plasticization effect of acids and water in PVA [16]. Dielectric and conduction properties of PVA complexed with H 3 PO 4 have been studied by Kufian et al [17]. Dielectric properties, vibrational and NMR studies on PVA doped with H 3 PO 4 and dielectric properties on PVA doped with H 2 SO 4 have been studied by Singh et al [18,19].…”
Section: Introductionmentioning
confidence: 94%
“…This is attributed to the increased amount of charge carriers, Li + ions from Li 2 SO 4 . [ 10,30 ] When the ratio of PVA:BMIMCl:Li 2 SO 4 is 1:3:2.2, the ionic conductivity of the FGPE reaches the maximum value (37 mS cm −1 ).…”
Section: Preparation and Properties Of Pva-bmimcl-li 2 So 4 Fgpementioning
confidence: 99%
“…Carbon allotropes were well known members of supercapacitor electrodes, [ 31,32 ] and PVA/H 3 PO 4 GPE is widely used due to its nontoxic nature and possible coupling of charge transport. [ 33,34 ] The GPE in the system serves as a separator, glue, electrolyte, and elastic skeleton component at once. The dual planar-helix supercapacitor wires do not require the additional loading of active materials or post treatment to increase their performance, which is another distinct advantage of this system over conventional wire-type supercapacitors from an engineering view point.…”
Section: (4 Of 8)mentioning
confidence: 99%